KEPRIBADIAN PENDIDIK MUSLIM DALAM PERSPEKTIF FILSAFAT PENDIDIKAN ISLAM - Annisa Riftah Andreani; Salminawati Salminawati; Usiono Usiono (Prodi PAI Sekolah Tinggi Agama Islam Serdang Lubuk Pakam, 2023)
The work of an educator is highly respected because it does more than impart knowledge; it is about guiding individuals to become individuals who are beneficial to themselves, their families and society. For a Muslim, noble character according to the teachings of the Qur'an and Hadith is his characteristic, especially in the context of Islamic education where educators are referred to by various terms that describe their role as mentors, teachers, moral shapers and guides. In this context, educators are not just ordinary people; they reflect rabbaniyah traits—traits that are reflected in their goals, behavior, and thought patterns—which are tasks given by Allah, the Messenger of Allah, parents, and teachers in Islamic education.